Computer anxiety and attitudes toward using Internet in English language classes among Iranian postgraduate student teachers - Bolandifar, Saeideh; Noordin, Nooreen (Universiti Putra Malaysia Press, 2015)
This study was designed to investigate the level of computer anxiety and the overall attitudes of Iranian postgraduate student teachers toward using the Internet in English language classes. Using a stratified random sampling, 160 participants (64 males and 96 females) were selected to take part in the study. These respondents were English language teachers who were pursuing their studies in Teaching English as a Second Language (TESL), English Literature, and Linguistics in public universities of Malaysia. A three-part questionnaire consisting of demographic information, Computer Anxiety Rating Scale (CARS) and Internet Attitude Scale (IAS) was administered in the data collection process. A pilot test was also conducted to achieve the reliability of the instruments. In order to strengthen the results, a semi- structured interview was conducted as well. The results indicated that the level of computer anxiety and the attitudes of the respondents toward using the Internet were of a moderate level. The findings of the independent-sample t-test showed significant mean differences between males and females and their level of computer anxiety and also their attitudes toward using the Internet. In addition, findings of the Pearson correlation coefficient revealed a significant negative relationship between computer anxiety and the participants' attitude toward using the Internet in their English language classes. Meanwhile, responses gauged through interview also supported the above findings. In conclusion, to eliminate the computer anxiety of teachers and encourage them to use the Internet technology in their classes, they should be equipped with sufficient technology skills through training programmes which can convince them about the usefulness of technologies in their instruction and create positive attitudes when using technology in the teaching and learning process.